Exploring Economic Potential in Religious Tourism Areas Through A Tourism Awareness Paradigm - Abdul Wakhid; Muhammad Syafi'i Budi Santoso; Zakiyyah Ilma Ahmad; Dimyati (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2025)
Background. This article discusses the economic potential in religious tourism areas in Indonesia through the tourism awareness paradigm. The tourism sector, particularly religious tourism, has become an important pillar in economic growth, contributing around 4.5% to the national Gross Domestic Product (GDP). Aim. With the increasing number of domestic and international tourists, religious tourism areas such as Borobudur Temple and Istiqlal Mosque show a significant impact on regional income and job creation. Method. This study uses a qualitative approach with the Systematic Literature Review (SLR) method to identify economic opportunities and existing challenges. Result. The results of the study show that the application of the tourism awareness paradigm can increase community participation in the management and preservation of religious sites, as well as encourage the development of supporting infrastructure. Empowering local communities through small and medium enterprises (SMEs) also plays an important role in achieving sustainable economic benefits. Thus, the development of religious tourism areas not only improves the welfare of the community, but also preserves local culture and traditions.